Influence of Leadership, Work Motivation, And Ability Work on Organizational Performance at Kendari Radio Frequency Spectrum Monitor Workshop Office - Suharyadi, Andi; Muthalib, Abdul Azis; Nur, Muh. (International Journal of Management and Education in Human Development, 2024)
This research aims to determine, test and analyze: (1) The influence of leadership, work motivation and work ability on organizational performance at Loka Monitor Spektrum Frequency Radio. (2) The influence of leadership on organizational performance at Loka Monitor Spektrum Frequency Radio. (3) The influence of work motivation on organizational performance at Loka Monitor Spektrum Frequency Radio. (4) The influence of work ability on organizational performance at Loka Monitor Spektrum Frequency Radio. The sample in this research were 39 employees at Loka Monitor Spektrum Frequency Radio. Data collection uses questionnaires. Data analysis uses multiple linear regression analysis. The research results show that: (1) Leadership, work motivation and work ability have a positive and significant effect on organizational performance at Loka Monitor Spektrum Frequency Radio. (2) Leadership has a positive and significant effect on organizational performance at Loka Monitor Spektrum Frequency Radio. (3) Work motivation has a positive and significant effect on organizational performance at Loka Monitor Spektrum Frequency Radio. (4) Work ability has a positive and significant effect on organizational performance Loka Monitor Spektrum Frequency Radio.